2014
DOI: 10.1007/s00520-014-2148-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemotherapy on quality of life in patients with non-small cell lung cancer

Abstract: It is now widely accepted that QoL should be considered as a primary endpoint of treatment in patients with advanced lung cancer both in clinical practice and clinical trials to further define meaningful response. As the traditional outcome measures of survival and tumour response are poor in this population, QoL assessment may offer a more comprehensive approach to evaluating the relative risks and benefits associated with treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 104 publications
0
26
0
3
Order By: Relevance
“…Results from the study showed that survival and quality of life was better in the chemotherapy-treated group 114 . Recently, a literature search showed that platinum-based regimens and even singleagent chemotherapy had a positive impact on quality of life and disease-specific symptoms 115 . This finding is in line with those of a survey in which 68% of patients preferred a therapy that would improve disease-related symptoms without prolonging their life as opposed to therapies that slightly prolonged their survival without improving symptoms 116 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Results from the study showed that survival and quality of life was better in the chemotherapy-treated group 114 . Recently, a literature search showed that platinum-based regimens and even singleagent chemotherapy had a positive impact on quality of life and disease-specific symptoms 115 . This finding is in line with those of a survey in which 68% of patients preferred a therapy that would improve disease-related symptoms without prolonging their life as opposed to therapies that slightly prolonged their survival without improving symptoms 116 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…During the past several decades, chemotherapy has been one of the most commonly used therapy approaches to treat various malignant tumors [1,2]. In the course of chemotherapy, some powerful antitumor antibiotics, such as, doxorubicin (DOX), paclitaxel, 10-hydroxycamptothecin, and cisplatin, are employed to suppress the proliferation of malignant cells, and then to relieve the pain symptom of patients and improve survival [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy side effects (CSE) have a considerable impact on quality of life (QOL) (Annunziata et al, 2013;Domati et al, 2015;Hwang et al, 2013;Mannion, Gilmartin, Donnellan, Keane, & Waldron, 2014;Wintner et al, 2013) and can severely impair a patient's ability to manage daily activities and employment. Moreover, unsatisfactory control of chemotherapy toxicities affecting treatment effectiveness necessitates dose reduction and/or treatment deferral (Havrilesky, Reiner, Morrow, Watson, & Crawford, 2015).…”
mentioning
confidence: 99%